Alteration of local adipose tissue trace element homeostasis as a possible mechanism of obesity-related insulin resistance. Issue 3 (September 2015) - Tinkov, Alexey A.; Sinitskii, Anton I.; Popova, Elizaveta V.; Nemereshina, Olga N.; Gatiatulina, Evgenia R.; Skalnaya, Margarita G.; Skalny, Anatoly V.; Nikonorov, Alexandr A.
Abstract The mechanisms of association between obesity and the related metabolic disturbances in general and insulin resistance in particular are extensively studied. Taking into account a key role of adipose tissue insulin resistance in the development of systemic obesity-related insulin resistance, the estimation of mechanisms linking increased adiposity and impaired insulin signaling in adipocytes will allow to develop novel prophylactic and therapeutic approaches to treatment of these states. A number of trace elements like chromium, zinc, and vanadium have been shown to take part in insulin signaling via various mechanisms. Taking into account a key role of adipocyte in systemic carbohydrate homeostasis it can be asked if trace element homeostasis in adipose tissue may influence regulatory mechanisms of glucose metabolism. We hypothesize that caloric excess through currently unknown mechanisms results in decreased chromium, vanadium, and zinc content in adipocytes. Decreased content of trace elements in the adipose tissue causes impairment of intra-adipocyte insulin signaling subsequently leading to adipose tissue insulin resistance. The latter significantly contributes to systemic insulin resistance and further metabolic disruption in obesity. It is also possible that decreased adipose tissue trace element content is associated with dysregulation of insulin-sensitizing and proinflammatory adipokines also leading to insulin resistance. We hypothesize that insulin resistance and adipokine dysbalance increase the severity of obesity subsequently aggravating alteration of adipose tissue trace element balance. Single indications of high relative adipose tissue trace element content, decreased Cr, V, and Zn content in obese adipose tissue, and tight association between fat tissue chromium, vanadium, and zinc levels and metabolic parameters in obesity may be useful for hypothesis validation. If our hypothesis will be confirmed by later studies, adipose tissue chromium, vanadium, and zinc content may be used as a prognostic biomarker of metabolic disturbances in obesity. Hypothetically, development and approbation of drugs increasing adipose tissue chromium, vanadium, and zinc content may help to achieve better metabolic control in obesity and obesity-related insulin resistance. However, stronger basis is required to prove our hypothesis. In particular, future studies should investigate the influence of obesity severity of adipose tissue trace element content, estimate the association between adipose tissue metals and metabolic parameters, and highlight the mechanisms involved in these changes. Both in vivo and in vitro studies are required to support the hypothesis.